Analysis of Damage to Caringin Cikukulu Road, Sukabumi District Using the Pavement Condition Index (PCI) Method - Paikun, Paikun; Perkasa, Rahmat Wisnu (ASTONJADRO, 2024)
Sukabumi Regency has a very important role in moving the economic and social wheels of society, so it needs to be supported by good flexible pavement conditions. Conditions based on Bina Marga 2020 data show that there are several roads that are heavily damaged in several sub-districts of Sukabumi Regency. Poor implementation, inappropriate planning, excessive traffic loads and standing water on the road surface are the causes of road damage, so to find out this requires a road damage analysis. For this research using the Pavement Condition Index (PCI) method. The results of this research show that the level of damage to all road surfaces studied according to the PCI method was taken from the average value of each STA, namely, the Caringin Cikukulu road section 62.25. So that the damage that has occurred to the road section does not become worse, it is necessary to immediately take repair action on the damaged units, so that it does not cause further damage. The choice of location for the author's research on the Caringin Cikukulu road was chosen because according to 2020 Bina Marga data the road was badly damaged.